2015
DOI: 10.1007/s13244-015-0459-0
|View full text |Cite
|
Sign up to set email alerts
|

MRI for the preoperative evaluation of femoroacetabular impingement

Abstract: Femoroacetabular impingement (FAI) refers to a condition characterized by impingement of the femoral head–neck junction against the acetabular rim, often due to underlying osseous and/or soft tissue morphological abnormalities. It is a common cause of hip pain and limited range of motion in young and middle-aged adults. Hip preservation surgery aims to correct the morphological variants seen in FAI, thereby relieving pain and improving function, and potentially preventing early osteoarthritis. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 60 publications
3
20
0
1
Order By: Relevance
“…The imaging techniques have been advanced to help surgeons for a more accurate assessment. The quantitative magnetic resonance imaging (MRI) of the cartilage, as delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) and T2 mapping, can map the concentration of glycosaminoglycans (GAGs) in the cartilage, so it provides high sensitivity and accuracy for detecting early damage and for follow-up of patients after conservative hip surgeries [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The imaging techniques have been advanced to help surgeons for a more accurate assessment. The quantitative magnetic resonance imaging (MRI) of the cartilage, as delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) and T2 mapping, can map the concentration of glycosaminoglycans (GAGs) in the cartilage, so it provides high sensitivity and accuracy for detecting early damage and for follow-up of patients after conservative hip surgeries [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,9,14,36 Another approach to studying the effects of FAI on hip joint health and function is through the use of magnetic resonance imaging (MRI) to assess articular cartilage degeneration in the FAI population. 11,19–21 Studies using MRI have demonstrated that there is a high incidence of hip joint cartilage abnormalities and labral lesions in the FAI population. 11,21 Gait assessments of patients with FAI during ADL may provide researchers and clinicians with the knowledge needed to detect this condition at an early stage and possibly reduce the need for surgical intervention.…”
mentioning
confidence: 99%
“…Furthermore, prolonged traction time may introduce a higher risk of nerve palsy and/or perioperative hypothermia on hip arthroscopic surgery, even though the traction time for one site was almost the same as that in single hip arthroscopy 18,19 . Therefore, we should carefully consider performing bilateral hip arthroscopic surgery si- rho, and T2 mapping, should also be considered 23 .…”
Section: Discussionmentioning
confidence: 99%